Strategi Manajemen Risiko dalam Menghadapi Tantangan Ketidakpastian di Pasar Global - Azzuhra, Dirra; Putri, Juliana (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This article discusses risk management strategies in the face of global market uncertainty triggered by the process of globalization and economic interconnection. Through a literature review, it highlights the importance of a proactive, flexible and collaborative approach that integrates various aspects such as politics, economics, technology and human resources. The use of modern technologies such as artificial intelligence (AI) and big data analysis is key in accelerating risk detection and appropriate decision-making. In addition, strengthening human resources, investment diversification, building risk reserves, and cross-departmental and external collaboration are considered key strategies to improve organizational resilience and competitiveness amid global uncertainty. The results of this study provide recommendations for organizations to adopt a comprehensive and sustainable approach to risk management to maintain business stability and sustainability in the era of globalization.